2016
DOI: 10.1016/j.neuroimage.2016.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of the posterior middle temporal gyrus in semantic cognition: Integration of anterior temporal lobe with executive processes

Abstract: Making sense of the world around us depends upon selectively retrieving information relevant to our current goal or context. However, it is unclear whether selective semantic retrieval relies exclusively on general control mechanisms recruited in demanding non-semantic tasks, or instead on systems specialised for the control of meaning. One hypothesis is that the left posterior middle temporal gyrus (pMTG) is important in the controlled retrieval of semantic (not non-semantic) information; however this view re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

59
347
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 344 publications
(410 citation statements)
references
References 79 publications
59
347
0
4
Order By: Relevance
“…The posterior MTG plays a key role semantic control processes (Binder & Desai, 2011; Davey et al, 2015; Davey et al, 2016; Noonan, Jefferies, Visser, & Lambon Ralph, 2013; Price, 2010) and is commonly implicated in studies of creativity (Gonen-Yaacovi et al, 2013; Shen et al, 2017). Recently, Davey et al (2016) investigated the functional role of the left posterior MTG in semantic control, and showed that the left posterior MTG integrates information from the DMN and ECN. In this context, higher modal controllability in the left posterior MTG may facilitate inhibition of salient responses during verbal creativity tasks, consistent with behavioral work linking inhibitory control and divergent thinking abilities (Benedek, Jauk, Sommer, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The posterior MTG plays a key role semantic control processes (Binder & Desai, 2011; Davey et al, 2015; Davey et al, 2016; Noonan, Jefferies, Visser, & Lambon Ralph, 2013; Price, 2010) and is commonly implicated in studies of creativity (Gonen-Yaacovi et al, 2013; Shen et al, 2017). Recently, Davey et al (2016) investigated the functional role of the left posterior MTG in semantic control, and showed that the left posterior MTG integrates information from the DMN and ECN. In this context, higher modal controllability in the left posterior MTG may facilitate inhibition of salient responses during verbal creativity tasks, consistent with behavioral work linking inhibitory control and divergent thinking abilities (Benedek, Jauk, Sommer, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Following from our prior studies (e.g. Davey et al, 2016, Gorgolewski et al, 2014, Smallwood et al, 2016), we did not use global signal regression but instead implemented component correction recommended by Murphy, Birn, Handwerker, Jones, and Bandettini (2009) which involves the extraction of the principle components in the white matter and the ventricles and controlling for these for the analysis of individual resting state scans.…”
Section: Discussionmentioning
confidence: 99%
“…One important aim for future studies will be identifying the extent to which there are patterns of resting state activity that are common to particular semantic tasks and others that discriminate between them. It would also be useful to examine how these putative semantic networks at rest are related to the spatial extent of the same networks as localised by online semantic task performance, allowing similarities and differences in the behaviour of semantic cognition networks to be characterised at rest and during tasks (for an example of this see Davey et al, 2016, Krieger-Redwood et al, submitted for publication). Our method may also aid the assessment of semantic cognition in populations such as children or patients, when measuring task performance can be problematic.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent meta-analysis based on activation likelihood estimation (ALE) revealed that brain activity in left and right IFG, left pMTG, pre-SMA and dorsal angular gyrus (dAG) bordering the intraparietal sulcus (IPS) was reliably associated with high control demands across a range of different semantic tasks (Noonan et al, 2013). This network is distinct from, yet partially overlapping with, the multiple-demand network which underpins executive control (Duncan, 2010): ventral LIFG and pMTG appear to have a relatively selective semantic focus, while dorsal PFC and IPS contribute to domain-general executive control (Davey et al, 2016, Krieger-Redwood and Jefferies, 2014, Noonan et al, 2013, Whitney et al, 2012). Regions implicated in semantic but not domain-general control may play a particularly crucial role in controlled memory retrieval: i.e., situations in which there is no explicit goal specifying which aspects of meaning must be selected, yet automatic spreading activation between related concepts is insufficient for efficient task performance.…”
Section: Introductionmentioning
confidence: 97%
“…Regions implicated in semantic but not domain-general control may play a particularly crucial role in controlled memory retrieval: i.e., situations in which there is no explicit goal specifying which aspects of meaning must be selected, yet automatic spreading activation between related concepts is insufficient for efficient task performance. Under these circumstances, it is the activation of conceptual representations that gives rise to the control demands (Davey et al, 2016, Jefferies, 2013). An example might be retrieving weak associations: the dominant aspects of meaning are likely to be irrelevant for identifying the context that links weakly-related words together and so control must be employed to focus retrieval on information relevant to this linking context.…”
Section: Introductionmentioning
confidence: 99%